Robinson - Sis, Peter. 1949- (New York : Scholastic Press, 2017)
Robin and his friends are planning to dress up as pirates for their school's annual costume party, but instead his mother creates a Robinson Crusoe costume for him, and while the adults love it, his friends are less welcoming.
Keywords: Crusoe, Robinson (Fictitious character) -- Juvenile fiction; Pirates -- Juvenile fiction; Costume -- Juvenile fiction; Friendship -- Juvenile fiction